Uso de herramientas tecnológicas para la enseñanza de la ciencias en educación media diversificada de acuerdo a la modalidad de estudio a distancia - Mervin Javier Rizales-Semprum; Carlos Luis Gómez-Valderrama; Cesar Augusto Hernández-Suarez (Ecomatemático, 2019)
The objective is to determine the use of a technological platform in diversified secondary education in accordance with the distance modality by science teachers in a Bolivarian High School in the state of Trujillo, Venezuela. The method was developed under a quantitative, descriptive, and field design approach. The sample was made up of eight teachers who teach science. The information was collected through a questionnaire. It was found that 37.5% of the respondents know how to use the Moodle platform. Another 25% said that they sometimes know how to use the platform. Likewise, 75% of the respondents feel that the distance learning mode is adequate for teaching the subject. It was evident that a significant group of teachers do not know about the Moodle platform and with it its usefulness in the teaching-learning process specifically in the interactive distance education mode